2013
DOI: 10.2486/indhealth.ms1364
|View full text |Cite
|
Sign up to set email alerts
|

The Increases in mRNA Expressions of Inflammatory Cytokines by Adding Cleaning Solvent or Tetrachloroethylene in the Murine Macrophage Cell Line J774.1 Evaluated by Real-time PCR

Abstract: The use of a petroleum-derived cleaning solvent for dry cleaning, instead of tetrachloroethylene (perchloroethylene, PCE), has increased. The cleaning solvent may induce immunological alteration. In this study, murine macrophage-lineage J774.1 cells were exposed to the cleaning solvent at 0, 25, 50, and 75 µg/ml or PCE at 0, 400, 600, 800, and 1,000 µg/ml by vigorous vortexing. Cell viability was determined. The mRNA expressions of tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β), IL-6, IL-10, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Targets were amplified on a LightCycler Nano (Roche Diagnostics) using LightCycler FastStart DNA Master PLUS SYBR Green I (Roche Diagnostics) over 40 cycles of denaturation at 94°, annealing at temperatures indicated in Table , and extension at 72°. Calibrator‐normalized cytokine to 18S rRNA relative ratio was calculated as the index of mRNA expression of each cytokine, following the manufacturer's protocols (Roche) …”
Section: Methodsmentioning
confidence: 99%
“…Targets were amplified on a LightCycler Nano (Roche Diagnostics) using LightCycler FastStart DNA Master PLUS SYBR Green I (Roche Diagnostics) over 40 cycles of denaturation at 94°, annealing at temperatures indicated in Table , and extension at 72°. Calibrator‐normalized cytokine to 18S rRNA relative ratio was calculated as the index of mRNA expression of each cytokine, following the manufacturer's protocols (Roche) …”
Section: Methodsmentioning
confidence: 99%
“…These data suggest possible mechanisms for tetrachloroethylene-induced perturbation of the immune response to allergens, and exacerbation of inflammation. An in vitro study by Kido et al (2013) also showed effects on pro-inflammatory cytokine gene expression. Significant (p<0.05) increases in the expression of IL-6…”
Section: Renal Effectsmentioning
confidence: 92%